Patronage and experiences of sexually abused Christian teenagers in "baby factories" in Nigeria - Uroko, Favour C. (International e-journal of criminal sciences, 2024)
This study examines the experiences and challenges that Christian teenagers who have been enslaved in baby factories are going through. The interviews for the study were conducted from 2022-2023 in Nigeria. Delta, Port Harcourt, and Enugu were chosen as the study areas because of the various cases of baby factory businesses that have been discovered in these areas. The study consisted of 19 teenagers who served as informants. The informants were between ages 10 and 30. This qualitative study was conducted with a critical discourse analysis (CDA) approach. Findings reveal that the factors that led to increased patronage of baby factories include less stringent requirements at baby factories, barren couples, no monitoring after adoption of the child, Christian teenagers lured under the deception of better lifestyles, and poverty. Also, the findings show that, as part of the experiences and challenges of teenagers in baby factories, some are forced to have sex with the men, their child is forcefully taken away, the teenager looks unhealthy and malnourished, she is not allowed to attend formal education, and she is paid less when she gives birth to a girl child compared to when she gives birth to a boy child. Recommendations were discussed.